Influence of Morphologically Superior and Inferior Trees on Germination, Storability and Seedling Performance of Neem (Azadirachta indica, A. Juss.) Seed - Kumar, Devendra; Mishra, Dhruv Kumar (Indian Forester, 2009)
A study was undertaken to find out the impact of physiologically superior and inferior neem (Azadirachta indica A. Juss.) trees on their seed performance in laboratory as well as in nursery. Germination percentage, mean germination time (MGT) and germination value were taken as seed parameters. Seedlings parameters taken were viz. total seedling length, number of leaves, collar diameter, total biomass and vigour index. Freshly collected seeds of both superior and inferior trees showed insignificant difference in respect of seed and seedling performance. Inferior trees showed significantly higher decline in seed performance as compared to superior trees after 30 and 60 days of storage. Seedlings raised from stored seeds of superior and inferior trees showed no effect on seedling performance. However, vigour index showed significantly lower value after storage seeds of inferior trees. Further, seed collected from inferior trees showed rapid seed deterioration in storage (P50, 172 days) as compared to superiors (P50, 271days).